Effect of solution on growth of zinc oxide tetrapod by thermal oxidation technique - Bhoomanee C. (2014)
In this work, the effects of solution on the growth of zinc oxide tetrapod (T-ZnO) were investigated. T-ZnO nanostructures were prepared by the thermal oxidation technique of metal zinc powder mixed with different solutions such as methanol (CH3OH), ethanol (C2H5OH) and hydrogen per oxide (H2O2). The mixtures were heated at the temperature of 1,000°C in normal atmosphere. A detailed field emission scanning electron microscopy (FE-SEM) showed that T-ZnO prepared by heating zinc and H2O2 gave the best tetrapodlike nanostructures. The length and diameter at the leg tip of T-ZnO is about 8.17 ± 1.17 μm and 47.8 nm, respectively. With this condition the highest percent yield of T-ZnO was about 4.82% by weight. Moreover, as determined by the energy dispersive spectroscopy (EDS), the atomic ratio of Zn and O was about 1:1. In addition, this study reveal that H2O2 acts as a strong oxidizing properties and has a role as a strong oxidizer to supply more reactive oxygen species to zinc in order to form T-ZnO.